2018
DOI: 10.1589/jpts.30.1333
|View full text |Cite
|
Sign up to set email alerts
|

Electrostimulation of the posterior tibial nerve in individuals with overactive bladder: a literature review

Abstract: [Purpose] This study aims to gather scientific evidence to identify whether clinical trials on Electrostimulation of the Posterior Tibial Nerve (ESPTN) in individuals with overactive bladder present an adequate methodological standard according to the PEDro (Physiotherapy Evidence Database) criteria. [Methods] Integral literature review, including randomized controlled clinical trials found in PEDro. [Results] We found 16 articles, of which only one did not meet the inclusion criteria. This article has shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Future studies should take age range into account, and further studies are needed to determine which treatment model would achieve better results in the treatment of elderly people. The limitation of this study is the 8 sessions of treatment, since studies usually treat OAB volunteers for 12 weeks (18). Even so, the information that patients can benefit from a reduced number of sessions is important in terms of the costs of treatment.…”
Section: ' Discussionmentioning
confidence: 99%
“…Future studies should take age range into account, and further studies are needed to determine which treatment model would achieve better results in the treatment of elderly people. The limitation of this study is the 8 sessions of treatment, since studies usually treat OAB volunteers for 12 weeks (18). Even so, the information that patients can benefit from a reduced number of sessions is important in terms of the costs of treatment.…”
Section: ' Discussionmentioning
confidence: 99%
“…6,7 The TTNS protocol is generally performed as weekly 30-min sessions for 12 weeks. 8 However, there are different protocols in the literature regarding the frequency of TTNS treatment. [9][10][11][12] There is only one study comparing the number of PTNS sessions in resistant OAB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Along with these advantages, it has been reported that its efficacy is similar to PTNS in the literature 6,7 . The TTNS protocol is generally performed as weekly 30‐min sessions for 12 weeks 8 . However, there are different protocols in the literature regarding the frequency of TTNS treatment 9‐12 …”
Section: Introductionmentioning
confidence: 97%
“…According to a systematic review [42] on scientific evidence of tibial nerve stimulation in individuals with OAB, one of the main findings was the poor methodological quality of the studies, which may interfere with its reliability and application in clinical practice, although the majority of sample numbers were considerable. The same authors [42] further discuss the need for better designed clinical trials on this therapy, which further strengthens the present investigation with this protocol.…”
Section: Discussionmentioning
confidence: 99%